Pengaruh Return On Equity (ROE), Non Performing Loan (NPL) Dan Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Nilai Perusahaan Bank BUMN - Marlina Marlina; Alwi Alwi; Amirulmukminin Amirulmukminin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the effect of Return on Equity (ROE), Non Performing Loan (NPL), and Operating Expenses to Operating Income (BOPO) on the firm value of State-Owned Commercial Banks (BUMN) listed on the Indonesia Stock Exchange (IDX). A quantitative approach with an associative research design was employed. The study utilized secondary data obtained from the annual financial statements of four state-owned banks during the 2021–2025 period, selected using a purposive sampling technique. Data were analyzed using SPSS version 26 through classical assumption tests, multiple linear regression analysis, correlation analysis, coefficient of determination, partial hypothesis testing (t-test), and simultaneous hypothesis testing (F-test). The findings reveal that Return on Equity (ROE) has a significant positive effect on firm value (p = 0.011), Non-Performing Loan (NPL) significantly affects firm value (p = 0.006), and Operating Expenses to Operating Income (BOPO) also has a significant effect on firm value (p = 0.004). Simultaneously, ROE, NPL, and BOPO significantly influence firm value, as indicated by an F-value of 10.426 with a significance level of 0.000. Furthermore, the coefficient of determination (R²) of 0.453 indicates that 45.3% of the variation in firm value can be explained by the three independent variables, while the remaining 54.7% is influenced by other factors outside the research model. These findings suggest that profitability, credit quality, and operational efficiency are key determinants of firm value and should be considered by bank management in improving corporate performance as well as by investors in making investment decisions.